Heme and iron limitation in a GI-tract foundation species leads to a reshuffling of the metalloproteome and a shift toward manganese usage - Rodrigues da Silva, Ronivaldo; Larson, James; Bothner, Brian; DuBois, Jennifer L. (Frontiers in Chemistry, 2025)
The metal-binding complement of the cellular proteome (the metalloproteome) depends on metal availability in the cellular environment and drives cellular metabolism. Bacteroides thetaiotaomicron (Bacteroides theta) is a foundational species in the anaerobic gut microbiome and a heme auxotroph, though little is known about why it requires heme. We hypothesized that B. theta would overproduce heme-binding proteins in response to limitations in non-heme iron, and reciprocally, activate non-heme iron pathways when heme was growth limiting. Here we showed that heme and/or non-heme iron scarcity triggers a more holistic reorganization of its metallome and metalloproteome. Under non-heme iron limitation induced by an Fe(II)-specific chelator, manganese supplementation restored growth, suggesting manganese can partly compensate for non-heme iron. Metalloproteomic analyses using tandem HPLC-ICP-MS revealed significant changes in the distribution of zinc, manganese, and iron in response to varying iron or heme availability. These findings highlight the interplay between heme/non-heme iron and the metallome in bacterial growth regulation, and they underscore a role for manganese under iron scarcity.